Gastroprotective and Immuno-supportive Role of Alcea kurdica against Stress Induced Lesion in Japanese Quails (Baghdad Science Journal, 2022)
The conducted research was done in Grda rasha field (Salahaddin University) for one month to compare the impacts of Alcea kurdica powder, Rifaxmine, and Ranitidine as anti-lesion and immune-strengthening agents on stress-induced quails which are affecting their growth rate and in severe cases causing gizzard erosion and deep intestinal lesions. To do that, 75 quails (12 weeks old) were grouped into six treatments with different additives. (T0-) = Negative control (Stress-induced Without treatment), (T0+) = Positive control (No stress inducing or treatment). T1= (treated with Rifaximine 200mg/L water mixed), T2= (treated with Ranitidine 200mg/L), T3= (treated with A.kurdica extract 100mg/L). The tested groups, except for positive control, were immersed in tap cold water (17°C) as a stress-induced technique. The Macroscopic analysis showed that quails pre-treated with A.kurdica extract (T3) had significantly (p<0.05) lower relative gizzard koilin layer disruption than those of T1, T2, and T0- groups, respectively. Moreover, the Elisa results indicated higher antibody titers against ND, IBD, and IB viruses for the T3 group with significantly increased HDL and lowered LDL, VLDL, and TCHO for T3 than that of T1, T2, T0+ T0- groups, respectively. Water mixed A.kurdica extract showed positive influences on the body weight, lipid profile, immune status and minimized gizzard erosions of breeding quails, which can be considered as a medicinal plant as well as a growth-enhancing agent in the poultry industry.